Child maltreatment and the risk of antisocial behaviour: A population-based cohort study spanning 50 years. (January 2020) - Degli Esposti, Michelle; Pinto Pereira, Snehal M; Humphreys, David K; Sale, Richard D; Bowes, Lucy
Abstract: Background: Child maltreatment is associated with an increased risk of antisocial behaviour; however, whether this risk persists and remains stable across the life-course is undetermined. Objective: To examine associations between chid maltreatment and antisocial behaviour across the life-course. Participants and setting: The study used 50 years of longitudinal data from the 1958 British birth cohort (n = 8088) measuring child neglect (prospectively) and abuse (retrospectively) and antisocial behaviour from childhood-to-adulthood. Methods: Latent growth curve models analysed the longitudinal course of antisocial behaviour across childhood (7–16years) and adulthood (23–50years) as a function of child maltreatment. We used directed acyclic graphs to identify, and adjust for, potential confounders (biological, family, social). Results: Child maltreatment was associated with higher levels of antisocial behaviour at all seven timepoints across the life-course (7–50years). Antisocial behaviour was elevated during childhood and adulthood in individuals who were maltreated, independently of confounding factors. Individuals who experienced multiple types of maltreatment were at the greatest risk of antisocial behaviour. Each additional maltreatment type was associated with an increased risk during both childhood (B = 0.173; SE = 0.024; p  < .001) and adulthood (B = 0.137; SE = 0.014; p  < .001). There was limited evidence that child maltreatment was associated with within-person rates of change, indicating that the increased risk of antisocial behaviour did not change over time. Conclusions: Child maltreatment is associated with an increased risk of antisocial behaviour, with a persistent and stable association remaining up to age 50. Our results highlight the burden of child maltreatment and the importance of providing long-term support for individuals who experience child maltreatment.